Reliability evaluation of substations subject to protection system failures - Fengli Wang; Tuinema, Bart W.; Gibescu, Madeleine; van der Meijden, Mart A. M. M. (2013 IEEE Grenoble PowerTech, 2013)
In power systems, substations play a key role in connecting generation and load centers to the grid. Substations are also a critical building block in connecting large-scale offshore wind and submarine interconnectors to the onshore grid. Therefore, reliability evaluation of substations is of great significance. Currently, most of the studies related to substation reliability only consider the substation connectivity and ignore the effects of protection system failures, which is not realistic. In this paper, the reliability of high-voltage substations subject to protection system failures is analyzed using event tree analysis. For this analysis, actual failure statistics from the Dutch power system are used. The influence of different substation configurations on the overall substation reliability is studied. This provides valuable insight about the reliability of different substation configurations, which can be useful for designing substations in the future power system.